2010
DOI: 10.1016/s1607-551x(10)70073-5
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis Infections in Southern Taiwan: A Multicenter Community‐based Study

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are major causes of liver disease in Taiwan and have a great impact on the health of this country. This study investigated the seroprevalence of HBV and HCV in southern Taiwan. Screening programs were performed from September 1999 to August 2005 for community-based surveillance of liver disease. A total of 28,797 adults from southern Taiwan, including Kaohsiung City (n = 14,036), Kaohsiung County (n = 7,713), and Pingtung County (n = 7,048) were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 27 publications
3
86
1
Order By: Relevance
“…Chronic hepatitis C (CHC) is one of the common infectious liver diseases and is a major global health problem (1). Hepatitis C virus (HCV) is recognized as the causative agent of CHC since its discovery in 1989 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis C (CHC) is one of the common infectious liver diseases and is a major global health problem (1). Hepatitis C virus (HCV) is recognized as the causative agent of CHC since its discovery in 1989 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Using that type of CKD screening method in young adults, for example, might reduce accessibility and, thus, the screening rate. This study is also the first to show that hepatitis B virus infection is associated with CKD in nonelderly patients in a hepatitis endemic area (25). It is well known that hepatitis B virus infection increases the risk for nephropathy (26); however, no previous study has identified its association with CKD.…”
Section: Discussionmentioning
confidence: 55%
“…It should be noted that Taiwan has a unique background, with the highest prevalence of uremia and endemic hepatitis B virus and hepatitis C virus infections (22). However, because MHD represents the major risk factor for ESRD patients, our findings are probably generalizable to other areas.…”
Section: Discussionmentioning
confidence: 65%